Peran Pancasila dalam Penyusunan Kebijakan Hukum Anti Terorisme: The Role of Pancasila in Preparing Anti-Terrorism Legal Policies - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Dyah Sekar Rengganis; Sofia Nuraini; Nurrohmar Tri Wulandari (Litera Academica Publishing, 2024)
Pancasila, as the state foundation and ideology of the Indonesian nation, plays a crucial role in formulating legal policies, including in efforts to eradicate terrorism. This article discusses how Pancasila values, such as justice, humanity and unity, are integrated into anti-terrorism legal policies in Indonesia. Pancasila provides a philosophical foundation that ensures the policy is not only effective in maintaining national security, but also respects human rights, prevents discrimination, and strengthens national unity. Thus, anti-terrorism policies prepared based on Pancasila are expected to realize law enforcement that is just, based on humanity, and supports the integrity of the Indonesian nation. The research method used is the Normative Juridical Approach method, this method focuses on literature studies and legal regulations, such as the Anti-Terrorism Law in Indonesia. Researchers usually analyze legislative documents, legal theory, and how Pancasila values are applied in existing legal policies. The results of this research reveal that a study of how Pancasila shapes anti-terrorism policy in Indonesia shows that the ideology and philosophy of Pancasila functions as an ideological and philosophical foundation.